Formulation and Characterization of Itraconazole as Nanosuspension Dosage Form for Enhancement of Solubility - Asmaa M. Rashid; Shaimaa N. Abdal-Hammid (College of Pharmacy University of Baghdad, 2019)
Abstract             Itraconazole is a triazole antifungal given orally for the treatment of oropharyngeal and vulvovaginal candidiasis, for systemic infections including aspergillosis, candidiasis,  and for the prophylaxis of fungal infections in immunocompromised patients.            The study aimed to formulate a practical water-insoluble Itraconazole, with insufficient bioavailability as nanosuspension to increase aqueous solubility and improve its dissolution and oral bioavailability.           Itraconazole nanosuspension was produced by a solvent-antisolvent nanoprecipitation method in the presence of different stabilisers (Poloxamer-188, HPMCE5) at different ratios with the drug alone or combination with surfactant(tween 80, SLS).          The results exhibit that the particle sizes of all prepared itraconazole formulations were in the nano size.  The best formula (F6) has a particle size.  ( 42  ) nm and Zeta potential of (- 21.86 ) mV.  In vitro cumulative release from the nanosuspension was (88 %) at (30) min when compared to the pure drug (13%) and lyophilized nanoparticles (98.2%) at (30)min. Effect of different parameters was investigated.           Fourier transforms infrared spectroscopy(FTIR), Differential scanning calorimetry (DSC) and X-ray diffraction (XRD), Scanning electron microscope( SEM) was done for the optimized  nanoparticles prepared by lyophilization technique         Thus, Nanosuspension appears to be an encouraging approach to formulate Itraconazole nanosuspension with high solubility and dissolution rate.               Keywords: Itraconazole, Nanoprecipitation method, Nanosuspension